Strategy for Accelerating Long School Expectations (LSE) and Average Lasting of School (ALS) in West Java - Fiyul, Arfiani Yulianti (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2024)
The purpose of this study is to analyze the acceleration of the Expected Years of Schooling (EYS) and Average Years of Schooling (AYS) in West Java. The region continues to face several educational challenges, including uneven distribution of quality and quantity of teachers, disparities in the management of educational institutions, inadequate facilities and infrastructure, and limited access to education, particularly in rural areas. These challenges hinder the effective acceleration of EYS and AYS, preventing them from meeting the expected targets. This study employs a qualitative approach using a case study method, with data collected through triangulation of observations, interviews, and documentation analysis. The study concludes that the strategy for accelerating EYS and AYS in West Java is implemented in an integrated manner involving the Provincial Education Office, the Regional Office of the Ministry of Religion of West Java Province, and Higher Education Service Institutions. Despite the coordinated efforts in planning, implementation, control, and assessment, various obstacles remain, and the results have not yet met expectations. This is the case even though substantial funding has been allocated, including Central and Regional School Operational Cost Assistance and through the Smart Indonesia Card.